Selenium deficiency and the effects of supplementation on preterm infants - Renata Germano B. O. N. Freitas; Roberto Jose N. Nogueira; Maria Angela R. G. M. Antonio; Antonio de Azevedo Barros-Filho; Gabriel Hessel (Sociedade de Pediatria de São Paulo, 2014)
Objective: This study aimed to review the literature about blood concentrations of selenium associated with gestational age, feeding, supplementation and related clinical features in preterm infants. Data sources: Systematic review in the following databases: MEDLINE, PubMed, Google academics, SciELO. org, ScienceDirect (Elsevier) and CINAHL-Plus with Full Text (EBSCO). Articles published up to January 2013 with the keywords "selenium deficiency", "selenium supplementation", "neonates", "infants", "newborn" and "preterm infants" were selected. Data synthesis: The studies reported that low blood selenium levels are associated with increased risk of respiratory diseases. Preterm infants, especially with low birth weight, presented lower selenium levels. Selenium deficiency has also been associated with the use of oral infant formula, enteral and parenteral nutrition (with or without selenium addition). The optimal dose and length of selenium supplementation is not well-established, since they are based only on age group and selenium ingestion by breastfed children. Furthermore, the clinical status of the infant affected by conditions that may increase oxidative stress, and consequently, selenium requirements is not taken into account. Conclusions: Prematurity and low birth weight can contribute to low blood selenium in premature infants. Selenium supplementation seems to minimize or prevent clinical complications caused by prematurity.